The Concept of the Demonic in Herkus Kunčius’s Novella A Most Loyal Metaphysical Friend and Marius Ivaškevičius’s Drama The Mistr - Čiočytė, Dalia (Colloquia, 2017)
There are two works of contemporary Lithuanian literature that effectively explore the theme of the demonic: Herkus Kunčius’s novella A Most Loyal Metaphysical Friend (Ištikimiausias metafizinis draugas, 2010) and the play The Mistr (Mistras, 2010), by Marius Ivaškevičius. The author of this article examines how these two works modify the traditional literary concept of the demonic – both works present the demonic not in classical, transcendental terms but as an immanent force. Considering the works from the perspective of literary theology, the author asks whether, and which kind of, theological thinking they develop. Herkus Kunčius’s novella is a postmodern metafiction (a fiction about a fiction): the central character of the narrative is the legendary Transylvanian vampire Count Dracula, the main character in Irish writer Bram Stoker’s gothic novel Dracula (1897). Kunčius’s Dracula is the creation of another character’s unhealthy consciousness – a “creation within a creation.” A parody of horror novels, films, etc. about vampires, the novella also parodies the language of psychiatrists, the characters who develop an idea about the demonic as an untreatable psychiatric illness: in the nihilistic reality of the work there simply is no one to treat it. Marius Ivaškevičius’s drama is a tragi-comical grotesque pasted together from Lithuanian historical and cultural symbols and analyzes the person of Adomas Mickevičius (1798–1855). In religious and cultural history, the prototype for Mistr in the play – Andrzej Towiański (1799–1878), a self-proclaimed prophet, “a mistr called by God” – represents the archetypical figure of the false prophet. The main meaning accorded to the demonic as represented in Ivaškevičius’s play is the demonic nature of political oppression: the work offers an original variation on the entanglement of political aggression and the demonic typically found in Lithuanian literature.